The Role of Generative AI in the Contemporary Art Ecosystem - Prabu Revolusi; Fauziah Shahab (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to explore the role of generative AI in the contemporary art ecosystem, from the process of creating artworks to their consumption by the public. As the use of AI technology in art continues to grow—whether in visual arts, music, or digital performance—it is essential to understand how this tool influences artistic practice, audience interaction, and the dynamics of the art market. This research employs a qualitative approach through the analysis of artworks generated with the assistance of AI. The focus includes how AI affects the artistic value and authenticity of artworks, as well as audience perceptions of AI-based creations. The findings of this study will reveal the opportunities AI creates in expanding artistic expression, alongside the challenges faced by artists regarding the human role in the creative process and its impact on the art economy. This research also aims to provide insights into the long-term effects of AI on the art industry, how these changes influence the art market, and how audiences engage with technology-based artworks. Thus, this study presents a comprehensive overview of the transformations brought by AI into the world of contemporary art.